Civil society participation in coastal resource management the case of Brgy. Lipata, Culasi, Antique. - Garachico, Marilou; Gleyo, Llofel (2000.)
The case of Barangay Lipata program represents an attempt to pursue shared responsibility between the government and local residents for managing and rehabilitating coastal resources. Some of the factors that provided the impetus for co-management arrangements were the recognition of the presence of resource management problems, dependence on coastal resources for livelihood and the desire for a more sustainable use. This study highlights the working relationships between government organizations (GOs), non-government organizations (NGOs) and participating coastal communities as they organize and involve themselves towards coastal resource rehabilitation and management in Brgy. Lipata. The study shows how strong partnership between non-government organization (NGO) and people's organization (PO) can facilitate program implementation.
Thesis (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo
Keywords: Coastal Resource Management -- Barangay Lipata, Culasi, Antique